Anterior inferior iliac spine avulsion fracture post hip arthroscopy for Femoroacetabular impingement. (October 2020) - Maalouly, Joseph; Aouad, Dany; Ayoubi, Rami; Dib, Nabil; Darwish, Mohammad; Saidy, Elias; Nehme, Alexandre
Abstract: FAI (Femoroacetabular Impingement) is an uncommon yet reported pathology of the hip joint, especially in the young athletic population. If left untreated, it predisposes for premature osteoarthritis of the hip. FAI treatment modalities consists of either open or arthroscopic surgery, the latter becoming the most adapted modality. We present a case of a young male athlete found to have FAI, treated arthroscopically. His post operative follow up was complicated by anterior inferior iliac spine avulsion fracture due to post op protocol non compliance which was treated with ORIF, with satisfactory non symptomatic outcome.